Desigualdad del hardware educativo en el Perú. El caso de los servicios básicos en las escuelas - Sánchez-Alcalde, Luis A. (2026)
The current study examines inequality in physical infrastructure and facilities available to students in public school in Peru, particularly with regard to utility systems (water supply, sewer system, electrical service). This was a cross-sectional study, as data were collected from schools located in 1,885 districts across Peru (the country’s basic unit of political division) for the year 2022. Using Principal Component Analysis and the K-means clustering algorithm, we identified territorial disparities among departments and regions. The findings indicate that districts located farther from the coastal region tend to have schools with greater deficiencies in basic utility services. Based on the above, it can be inferred that Peru comprises at least four distinct contexts according to the quality of physical infrastructure and basic utility services in schools. Consequently, education policy should be revised to address these diverse contexts instead of relying solely on the current regional and decentralised approach.